First record of borrelia spielmani in Turkey [Türkey'de idot;lk borrelia spielmani bulgusu] - (:unkn) unknown (My University, 2010)
The almost worldwide distribution of Borrelia burgdorferi sl spirochaetes promotes the association with different tick species and thus different epidemiological pattern can be observed. Seven B. burgdorferi genospecies are currently recognized in Europe. Two of them (B. bissettii and B. spielmani) are still poorly characterized and most details about distribution are ignored. This paper reports the PCR detection of B. spielmani in a tick in the city of Istanbul (Turkey) collected while biting a human. This genospecies was previously known from The Netherlands, Germany, France, Hungary and Slovenia. This finding contributes to the further knowledge of the distribution of the different genospecies of B. burgdorferi sl.
Keywords: B. burgdorferisl; Tick; Turkey